2002
DOI: 10.1086/340340
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Flaring in the Pre–Main‐Sequence Sun and Implications for the Early Solar System

Abstract: To address the role of energetic processes in the solar nebula, we provide a detailed characterization of magnetic flaring in stellar analogs of the pre-main-sequence Sun based on two 0.5 day observations of the Orion Nebula cluster obtained with the Chandra X-Ray Observatory. The sample consists of 43 stars with masses between 0.7 and 1.4 M and ages from less than 0.3 to '10 Myr. We find that the X-ray luminosities measured in the 0.5-8 keV band are strongly elevated over main-sequence levels with an average … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
203
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(220 citation statements)
references
References 91 publications
17
203
0
Order By: Relevance
“…These same flares occur at a rate about 10 2.5 higher than the rate of the largest solar flares. As solar proton fluxes scale non-linearly with the solar X-ray luminosity, Feigelson et al (2002) estimated a proton flux for "T Tauri Sun" about 10 5 times higher than at present (i.e., 10 7 protons cm −2 s −1 at 1 AU). Given the high flare rate, this flux was probably present almost continuously.…”
Section: Stellar High-energy Particlesmentioning
confidence: 88%
See 1 more Smart Citation
“…These same flares occur at a rate about 10 2.5 higher than the rate of the largest solar flares. As solar proton fluxes scale non-linearly with the solar X-ray luminosity, Feigelson et al (2002) estimated a proton flux for "T Tauri Sun" about 10 5 times higher than at present (i.e., 10 7 protons cm −2 s −1 at 1 AU). Given the high flare rate, this flux was probably present almost continuously.…”
Section: Stellar High-energy Particlesmentioning
confidence: 88%
“…Feigelson et al (2002) estimated the proton flux at 1 AU of a solar analog in its T Tauri phase, from a statistical X-ray study of T Tauri stars in the Orion Nebula Cluster. They found that frequent flares on T Tauri stars are 10 1.5 times more luminous than the largest solar flares (or 10 4 times more than solar flares that occur with a daily frequency).…”
Section: Stellar High-energy Particlesmentioning
confidence: 99%
“…In particular, Feigelson and his colleagues have consistently presented both observational and theoretical evidence that they must occur (see recent report by [287]). There are extensive recent studies of irradiation models referred to earlier in the text.…”
Section: Conclusion and Major Problems -Potential And Realmentioning
confidence: 96%
“…As regards the second feature that the flare activity may explain: both the anomalous abundances of elemental isotopes in chondrules and the inclusions of the most pristine carbonaceous chondrites, as well as the high abundances of daughter products of some short-lived nuclides, all point to high-energy processes that occurred during the early stages of our Solar System (see, e.g., Feigelson et al 2002;Gounelle et al 2001). Although external phenomena, like supernova explosions, have been used to explain these abundances, it has been suggested that they could also be due to spallation reactions from energetic (MeV) protons and ions originating in magnetic reconnection flares (see also Goswami et al 2001;Marhas et al 2002;Leya et al 2003).…”
Section: Effects Of Flares On Young Planetary Systemsmentioning
confidence: 99%